Design of IoT-Based Temperature and Humidity Monitoring System to Support Work Environment Safety in Furniture Workshop - Nuskha Ilma Arini; Niki Etruly; Juliasari Prasetya (Universitas Ibn Khaldun Bogor, 2024)
The furniture industry is one of the sectors with high risks to the health and safety of workers. Permenaker No. 5 of 2018 establishes comfortable working temperature standards between 18°C - 28°C, with humidity levels between 40% - 60%. Uncontrolled temperature and humidity conditions in furniture workshop environments can lead to various health and safety issues, including dehydration, fatigue, decreased concentration, and increased risk of workplace accidents. The furniture workshop is a learning facility at Polifurneka, equipped with various machines for furniture production processes. To ensure a safe working environment in the Polifurneka furniture workshop, a system is needed to measure working conditions in real time. This allows workshop managers to identify high-risk areas and take appropriate preventive actions. One preventive measure that can be implemented is the development of an Internet of Things (IoT)-based temperature and humidity monitoring system. This study develops an IoT-based temperature and humidity monitoring system to monitor working conditions in the furniture workshop using two types of sensors: DHT 11 and DHT 22 sensors. From the test results of these two sensors, DHT 22 sensor demonstrates a higher accuracy level, both for temperature and humidity readings compared to the DHT 11 sensor.